Modulatory Effect of 4-(methylthio)butyl Isothiocyanate Isolated From Eruca Sativa Thell. on DMBA Induced Overexpression of Hypoxia and Glycolytic Pathway in Sprague-Dawley Female Rats - Singh, Davinder; Thakur, Sharad; Singh, Drishtant; Buttar, Harpal Singh; Singh, Balbir; Arora, Saroj (Frontiers in Pharmacology, 2021)
4-(methylthio)butyl isothiocyanate (4-MTBITC) is a hydrolytic product from the plant Eruca sativa Thell. In the present study, we explored the anti-cancer effect of 4-MTBITC against 7,12-dimethylbenz[a]anthracene (DMBA) induced breast cancer. Hypoxic conditions were developed using a single dose of 60 mg/kg DMBA. Hepatic and renal parameters were increased along with antioxidants in cancer-bearing rats which were lowered with the treatment of 4-MTBITC. Further, it inhibited the up-regulation of glycolytic enzymes caused by DMBA. The hypoxia pathway was evaluated using RT-PCR and it was found that the 40 mg/kg doses of 4-MTBITC statistically lowered the expression of HIF-1α. Akt/mTOR signaling pathway was one of the major pathways involved in 4-MTBITC-induced cell growth arrest by western blotting. Amino acid profiling serum-free plasma revealed the downregulation of specific amino acids required for vital components of fast-growing cancer cells. 4-MTBITC reduced the levels of serine, arginine, alanine, asparagines, and glutamic acid. Histological examination also showed neoplastic growth following DMBA doses. 4-MTBITC treated rats showed less infiltration and normal physiology. Our findings for the first time demonstrated the potential therapeutic significance of 4-MTBITC on modulation of glycolytic enzymes and hypoxia pathway in female rats.